2017
DOI: 10.18203/2319-2003.ijbcp20170814
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of analgesic activity of turmeric (Curcuma longa Linn.) in Wister rats

Abstract: Background: NSAIDs like Aspirin etc. are randomly used for mild to severe types of pain but long-term and injudicious use of NSAIDs lead to a number of side effects. The present study is designed for exploring the analgesic potential of Curcuma longa Linn (Turmeric) in albino rats, which may widen the therapeutic horizon for the said agent.Methods: Ethanolic extract of Curcuma longa in the doses 100, 200 and 400mg/kg is given orally to 6 Wister rats against a control of normal saline and a standard using Aspir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 7 publications
0
9
0
3
Order By: Relevance
“… 24 In animal models, C longa rhizome extracts were also examined for analgesic and antipyretic activities, and the rhizome extracts showed effective potency on analgesic effect. 25 C citratus is another widely used herb in folklore and traditional medicine. The chemical constituents of essential oil have been examined and it was found that geranial, neral, and myrcene were 3 main active constituents.…”
Section: Discussionmentioning
confidence: 99%
“… 24 In animal models, C longa rhizome extracts were also examined for analgesic and antipyretic activities, and the rhizome extracts showed effective potency on analgesic effect. 25 C citratus is another widely used herb in folklore and traditional medicine. The chemical constituents of essential oil have been examined and it was found that geranial, neral, and myrcene were 3 main active constituents.…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin has several beneficial activities such as antioxidant, antimicrobial, anti-inflammatory, analgesic, nephroprotective, and chemotherapeutic properties. [14][15][16][17][18][19][20][21] As amyloid plaques cause oxidative damage to the brains of the AD patients, also generation of free radicals by Aβ, abnormalities in the mitochondria of the cells, inflammation and abnormal changes which affects the natural antioxidant defense are ultimately responsible for the pathophysiology of AD. [22] Thereby, substances which have antioxidant properties like curcumin can be potential therapeutic targets useful in slowing the disease progression.…”
Section: Introductionmentioning
confidence: 99%
“…al., 2018). Studi yang dilakukan pada tikus dengan memberikan ekstrak kunyit sebanyak dosis 400 mg/kg meunjukkan aktivitas analgesik yang signifikan pada tikus dan aktivitas analgesiknya sebanding dengan aspirin pada 90 dan 120 menit (Jogdand and Bhattacharjee, 2017). Penelitian lain menyebutkan bahwa ekstrak air kunyit dapat mengurangi peradangan akut pada telinga tikus yang dibuat edema, efek ekstrak air kunyit sebanding dengan curcuminoid dan tumeron (Bagad, et.…”
Section: Pendahuluanunclassified